DEVELOPING A CULTURAL ENCYCLOPEDIA BOOK BASED ON THE LOCAL WISDOM OF BANTEN ON SOCIAL SCIENCE SUBJECT AT GRADE IV ELEMENTARY SCHOOL - Nurul Khotima; Ana Nurhasanah; Damanhuri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to develop a cultural encyclopedia book based on the local wisdom of Banten on social scence subject at the 4 th grade elementary school. This research was conducted at grade IV SD Negeri Rawu. This research used research and development methods (RnD). The product of this research was a cultural encyclopedia book containing materials about historical heritage in the local environment for social science subject at grade 4. The feasibility of this product was validated by some experts including media experts, material expert, linguists, and education experts. This research subjects were 20 grade IV students at SD Negeri Rawu. The results showed that the average validation score of the encyclopedia was 90.57%, so that it was categorized as“very feasible”. Then, the result of product trials (limited trials) obtained that the average value of the product was 99.05% with a “very good” criteria, so it can be concluded that the cultural encyclopedia book based on the local wisdom of Banten was feasible to be used as learning materials for social science subject at grade IV elementary school.